The complete chloroplast genome of dalmatian pyrethrum (Tanacetum cinerariifolium (Trevir.) Sch. Bip. (Asteraceae)), the source of the natural insecticide pyrethrin - Ante Turudić; Zlatko Liber; Martina Grdiša; Jernej Jakše; Filip Varga; Zlatko Šatović (Mitochondrial DNA. Part B. Resources, 2022)
Tanacetum cinerariifolium is an endemic species of the eastern Adriatic coast that synthesizes the natural insecticide pyrethrin. We have characterized the complete chloroplast genome of the species and analyzed its phylogeny within the Asteraceae family. The complete chloroplast genome of T. cinerariifolium has a size of 150,136 bp, including a large single-copy (LSC) region of 82,717 bp, a small single-copy (SSC) region of 18,411bp, and a pair of inverted repeats (IRs) of 24,504 bp. The chloroplast genome of T. cinerariifolium encodes 108 genes, including 77 protein-coding genes (PCGs), 27 tRNA genes, and 4 rRNA genes. Phylogenetic analyses based on the complete chloroplast genomes placed T. cinerariifolium in a sister position to species of the genera Artemisia and Chrysanthemum.